Bent and twisted: the electronic structure of 2-azapropenylium ions obtained by guanidine oxidation - Hornung, Julius; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (RSC Advances, 2016)
New bis-2-azapropenylium ions are obtained by oxidation of guanidino-substituted aromatic compounds. The dications 12+ (1 = 1,4-bis-tetramethylguanidinobenzene) and 22+ (2 = 1,4-bis-guanidinobenzene) exhibit unexpected bent-twisted structures, that differ from the known 2-azapropenylium ion structures (linear-orthogonal 2-azaallenium ion or bent-planar 2-azaallylium ion), and resemble the structures of carbodicarbenes. Their electronic structure was analysed by a combination of experiments and quantum chemical calculations. The results indicate that the bent-planar structure is disfavoured for steric reasons, while the allene-type linear-orthogonal structure is also disfavoured due to the electron-donating groups that support the bent form. For these reasons a bent-twisted structure is adopted, in which the nitrogen atom is engaged with two different orbitals in π-bonding with the carbon π-system and in a weaker π-interaction with the CN2 group of the guanidino system.
Gesehen am 20.05.2020